The crisis as an opportunity for change? High-skilled immigration policies across Europe. Issue 10 (8th August 2016) - Cerna, Lucie
ABSTRACT: The recent economic crisis provided a shock to the system, and led governments to scramble for solutions to problems of falling economic growth, high unemployment and weak job creation. Many European governments responded to protectionist calls by restricting immigration policies, even towards the highly skilled. Yet countries have faced different challenges and thus the cross-national variation in the demand for policy closure or openness is remarkable. Some seized the opportunity to restrict their high-skilled immigration policies, while others took advantage of the crisis for further liberalisation. The article explores different reasons for this variation, ranging from socio-economic conditions, the inflow of labour migrants to the role of labour market institutions and political actors. Countries badly affected by the crisis and with a recent influx of labour migrants were more likely to respond to mobilised groups lobbying for restrictive policies than those countries weathering the crisis relatively better but suffering from continuing labour shortages. The article examines the changing conditions and the role of mobilised stakeholders to explain policy change in selected European countries. It also presents an updated index on states' openness to high-skilled immigrants to measure change over time. The findings are based on position statements of stakeholders, official documents and media coverage.